Salidroside mitigates hydrogen peroxide-induced injury by enhancement of microRNA-27a in human trabecular meshwork cells - Jun Zhao; Xiujuan Du; Meng Wang; Peiyao Yang; Juanmei Zhang (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Salidroside (Sal) exerted widely pharmacological effects in multitudinous diseases had been certified. The actual study clarified the protective activity of Sal in H2O2-injured human trabecular meshwork (HTM) cells. HTM cells were disposed with H2O2 to construct an oxidative damage model in vitro. Then, Sal was utilized to administrate HTM cells, and cell viability, apoptosis, apoptosis-interrelated proteins and ROS production were appraised using CCK-8, flow cytometry, western blot and DCFH-DA staining. MiR-27a inhibitor and its control were transfected into HTM cells, and the influences of miR-27a inhibition in HTM cells stimulated with H2O2 and Sal were detected. PI3K/AKT and Wnt/β-catenin pathways were ultimately investigated to uncover the underlying mechanism. We found that H2O2 evoked HTM cells oxidative damage, as evidenced by repressing cell viability, inducing apoptosis, activating cleaved-caspase-3/-9 expression and increasing ROS production. Sal significantly lightened H2O2-evoked oxidative damage in HTM cells. Additionally, miR-27a was up-regulated by Sal, and miR-27a suppression significantly reversed the protective effect of Sal on H2O2-injured HTM cells. Finally, Sal activated PI3K/AKT and Wnt/β-catenin pathways through enhancement of miR-27a in H2O2-injured HTM cells. In conclusion, these discoveries suggested that Sal could protect HTM cells against H2O2-evoked oxidative damage by activating PI3K/AKT and Wnt/β-catenin pathways through enhancement of miR-27a.HighlightsH2O2 evokes HTM cells oxidative damage;Sal relieves H2O2-induced oxidative damage in HTM cells;Sal enhances miR-27a expression in H2O2-injured HTM cells;Repressed miR-27a reverses the protective impacts of Sal on H2O2-injured HTM cells;Sal activates PI3K/AKT and Wnt/β-catenin pathways by increasing miR-27a.